Asclepias curassavica Butterflyweed, Milkweed, Silkweed - Edward F. Gilman; Ryan W. Klein; Gail Hansen (EDIS, 2018)
Butterfly weed is a member of the milkweed family and by some reports, the only Asclepias that does consistently well in south Florida. Original publication date October, 1999. This revision by Ryan W. Klein and Gail Hansen, August 2018.